Two‐Step Carbothermal Synthesis of AlN–SiC Solid Solution Powder Using Combustion Synthesized Precursor. Issue 4 (26th December 2014) - Chu, Aimin; Qin, Mingli; ud‐din, Rafi; Dong, Yinghu; Guo, Shibo; Qu, Xuanhui; Parthasar, T.
<x xml:space="preserve">Abstract</x> In the present work, a two‐step carbothermal reduction method is employed to prepare the AlN–SiC solid solution (AlN–SiCss) powders by using a combustion synthesized precursor. The precursor is prepared by low‐temperature combustion synthesis (LCS) method using a mixed solution of aluminum nitrate, silicic acid, polyacrylamide, glucose, and urea. The synthesized LCS precursor exhibits a porous and foamy uniform mixture of Al2O3 + SiO2 + C consisting of flaky particles. The carbothermal reduction in the LCS precursor is carried out in two steps. First, the precursors are calcined at 1600°C in argon for 3 h. Subsequently, the precursors are further calcined at 1600°C–1900°C in nitrogen for 3 h. The results indicate that the precursor calcined at and above 1850°C in nitrogen for 3 h yields the single‐phase AlN–SiCss powders. The synthesized AlN–SiCss powder exhibits near‐spherical particles with diameter of 200–500 nm. The experimental and thermodynamical results reveal that the formation of AlN–SiCss occurs via the diffusion of AlN into SiC by virtue of formation of a highly defective β′ intermediate during the second step reaction.